PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV SDN 020 PADANG MUTUNG KECAMATAN KAMPAR - Amriani, Amriani; Marhadi, Hendri; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was motivated by the low learning outcomes Civics fourth grade (IV) students SDN 020 Padang Mutung with average value 60.68 (with KKM 70). The purpose of this research was to improve civics learning outcomes of the fourth grade (IV) students of SDN 020 Padang Mutung Kampar districts with the implementation of cooperative STAD type learning model. This research was classroom action with two cycles. The subjects were students of class IV SDN 022 Padang Mutung academic year 2015/2016 whict amounted to 22 people consisting of 10 male students and 12 female students. Based on the result an analysis the observation of teachers and students' activity sheet has increased at every meeting. Teacher’s activity with the implementation of cooperative STAD type learning model at first meeting of the first cycle was 66.66% (good), and the second meeting of the first cycle of 75% (good), At second cycle, Teacher’s activity at first meeting of first cycle was 91.66% (very good ) and the second meeting was 95.83% (very good). Students activities at first meeting of the first cycle was54.16% (enough) and the second meeting was 70.83% (good), At second cycle, student activities at first meeting was 83.33% (very good), and second meeting was 95.85 % (very good). Civics learning outcomes before implementation cooperative STAD type learning model average 60.68, after implementation of cooperative STAD type learning model (UH) I was 68.40 that improve of 12.72% , and the UH II was 82.95 that improve of 36.36%. Based on this it can be concluded that the application of cooperative STAD type learning model can improved civics learning outcomes of the fourth grade (IV) students students SDN 020 Padang Mutung Kampar District.Keywords: Cooperative Learning Model Type stad, Civics studies students achievement